Preferential Th1 Cytokine Profile of Phosphoantigen-Stimulated Human V?9V?2 T Cells - Dunne, Margaret; MANGAN, BOZGANA; DOHERTY, DEREK (Hindawi, 2010)
Human V?9V?2 T cells recognise pyrophosphate-based antigens (phosphoantigens) and have multiple functions in innate and adaptive immunity, including a unique ability to activate other cells of the immune system. We used flow cytometry and ELISA to define the early cytokine profiles of V?9V?2 T cells stimulated in vitro with isopentenyl pyrophosphate (IPP) and (E)-4-hydroxy-3-methyl-but-2 enyl pyrophosphate (HMB-PP) in the absence and presence of IL-2 and IL-15. We show that fresh V?9V?2 T cells produce interferon-? (IFN-?) and tumour necrosis factor-? (TNF-?) within 4 hours of stimulation with phosphoantigen, but neither IL-10, IL-13, nor IL-17 was detectable up to 72 hours under these conditions. Cytokine production was not influenced by expression or lack, thereof, of CD4 or CD8. Addition of IL-2 or IL-15 caused expansion of IFN-?-producing V?9V?2 T cells, but did not enhance IFN-? secretion after 24-72 hours. Thus, phosphoantigen-stimulated V?9V?2 T cells have potential as Th1-biasing adjuvants for immunotherapy.
PUBLISHED
Keywords: Immunology; T Cells